Application of microneedles for the treatment of nodular basal cell carcinoma - Bin Sabri, Akmal Hidayat (2021)
Basal cell carcinoma (BCC) is one the most common skin cancer in humans. One of the most efficacious drugs used in treating BCC is imiquimod, which is available as a topical cream, AldaraTM. Nevertheless, the drug has limited cutaneous permeation limiting its use only for the management of superficial BCC. The work presented in this thesis explored the utility of microneedles as a drug delivery platform for the intradermal delivery of imiquimod for the treatment of nodular BCC. This was achieved by first comparing the insertion profiles of two commercial microneedle systems, the DermastampTM and Dermapen®. It was discovered that the oscillating microneedle system, the Dermapen® required less force than the Dermastamp™ to puncture the skin while resulting in deeper insertion in ex vivo skin tissue to a depth needed to treat nodular BCC. Moving forward, the effectiveness of the Dermapen® to improve the delivery of imiquimod into the skin was investigated. It was discovered that post-treatment of the skin with the Dermapen® after AldaraTM application, known as “patch-and-poke”, enhanced the intradermal delivery of imiquimod generating a depot that that persisted for up to 24 hours. However, such enhancement was not achieved when a “poke-and-patch” strategy was adopted, where skin was pre-treated with the Dermapen® prior to cream application. Despite the effectiveness of the “patch-and-poke” strategy in delivering imiquimod intradermally, this approach may not be acceptable by patients owing to the two-step nature of the treatment. In order to overcome this limitation a one-step drug delivery strategy utilising dissolving polymeric microneedles was explored. This was achieved by fabricating a dissolving microneedle system out of the commercial PVPVA polymer, Kollidon® VA 64. The dissolving microneedle system demonstrated the capability of delivering similar quantities of imiquimod but into the deeper layers of the skin, despite a 6-fold lower drug loading, relative to the current clinical dose of Aldara™ cream used in BCC treatment. Furthering this, a series of polymeric microneedles of different designs and polymer chemistries were manufacture from pAMPS, pNAM and pHEAM that were synthesised via free radical polymerisation reactions. Drug release studies into ex vivo porcine skin tissues and ex vivo patient BCC tumours demonstrated that the pNAM obelisk microneedle patches were capable of achieving higher intradermal delivery of imiquimod relative to the commercial cream, AldaraTM. In addition, an in vivo tumour efficacy study using a mouse model for skin tumours highlighted that the microneedle patches were capable of slowing down tumour growth. Lastly, this thesis demonstrated the analytical capability offered by time-of-flight secondary ion mass spectrometry (ToF-SIMS) in evaluating the effectiveness of microneedle-based drug delivery systems. This is exemplified by the ability of the instrument to track the dermal distribution of active (imiquimod) and excipients (polymers and surfactant) from different formulations within biological tissues in a label free fashion. Such unprecedented analysis enabled us to demonstrate active-excipient colocalisation thus expanding our mechanistic insight on how such delivery systems behave upon administration into the skin. Overall, this thesis expanded our knowledge on how some microneedle systems are capable of achieving enhanced intradermal delivery while highlighting the viability of this drug delivery platform for the treatment of nodular BCC in a minimally invasive fashion